Toxicological and Haematological Effects of Senna alata Extract on Clarias gariepinus Fingerlings - Eteng, Arikpo Okoi; Jehu, Auta; Mohammed, Ndagi Abubakar; Yusuf, Abdulateef; Bello, Muhammad Onimisi; Ikpi, Gabriel Ujong (Tecno Scientifica Publishing, 2025)
The study evaluated the acute and sub-lethal effects of ethanol extract of Senna alata stem bark on physicochemical parameters and haematological indices of Clarias gariepinus fingerlings. A 96-hour acute toxicity bioassay established an LC₅₀ of 11.54 mg/l (95% CI: 10.92–12.16 mg/l) and an LC₉₉ of 23.30 mg/l (95% CI: 21.75–24.85 mg/l), with mortality increasing from 0% in the control to 85% at 12.6 mg/l. Sub-lethal concentrations (0.61, 0.71, and 0.81 mg/l, corresponding to 1/20th, 1/16th, and 1/14th of LC₅₀, respectively) were applied for eight weeks. Physicochemical parameters (pH, temperature, total dissolved solids, electrical conductivity, and dissolved oxygen) were monitored before and after extract application. Electrical conductivity differed significantly at 0.61 mg/l (p = 0.0351), while other parameters remained statistically unchanged, although dissolved oxygen declined progressively with increasing concentration. Haematological analysis revealed no significant changes (p > 0.05) in haemoglobin, mean corpuscular haemoglobin, mean corpuscular volume, packed cell volume, platelet, red blood cell, and white blood cell counts, except for a significant alteration in mean corpuscular haemoglobin concentration (p = 0.0479). These findings demonstrate that S. alata exhibits moderate piscicidal toxicity under acute exposure and induces mild physiological stress under sub-lethal conditions, which could have long-term implications for fish health and aquaculture productivity. The use of S. alata as a piscicide should therefore be approached cautiously to prevent unintended ecological consequences. Future studies should evaluate histopathological and biochemical stress responses to establish environmental safety limits for S. alata in aquaculture systems.